2017
DOI: 10.1590/1676-0611-bn-2016-0236
|View full text |Cite
|
Sign up to set email alerts
|

Phanerogamic flora and vegetation of Itacolomi State Park, Minas Gerais, Brazil

Abstract: Located in the municipalities of Ouro Preto and Mariana, in the Quadrilátero Ferrífero (QF) of Minas Gerais, the Itacolomi State Park (ISP) shelters more than 7,000 ha of remnants of Atlantic Forest and campos rupestres. The QF region has high biodiversity and is being highly impacted, mainly by mining activities. Aiming to organize the available floristic information and to support related research, this study presents the list of phanerogamic species of the ISP and the major vegetation types. This survey was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
0
7
1
Order By: Relevance
“…León (2010) found that several species of the genus Ficus (Moraceae) have high index of importance of plants values, being important for seed dispersion. However, plants of this genus were uncommon in the PEIT areas (Messias et al, 2017), not being recorded in the interactions observed in the present study.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…León (2010) found that several species of the genus Ficus (Moraceae) have high index of importance of plants values, being important for seed dispersion. However, plants of this genus were uncommon in the PEIT areas (Messias et al, 2017), not being recorded in the interactions observed in the present study.…”
Section: Discussioncontrasting
confidence: 60%
“…Precipitation is concentrated between the months of October and March, with a notorious wet season during summer and another dry season in winter (Tafuri, 2008). In the PEIT, rupestrian grasslands occupy 51% of its territory (3,846.93 ha), 40% is covered by montane Atlantic Forest (3,017.2 ha), and 9% is occupied by a 30-years abandoned eucalyptus plantation (two blocks totaling 678.87 ha), placed in an area previously occupied by the native Atlantic Forest, as long as abandoned tea plantations and human constructions (Messias et al, 2017). In this protected area, have being recorded 1,623 plant species, 251 birds, 43 mammal species, 37 amphibians and 22 reptiles, showing its high biodiversity (Governo do Estado de Minas Gerais et al, 2007;Messias et al, 2017).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The present study was conducted at the Engenho D'Água farm, located in São Bartolomeu district (20º15'41" S, 43º36'34" W), Ouro Preto municipality, Minas Gerais, southeastern Brazil. The study area's vegetation is classified as semideciduous seasonal forest within the Atlantic Forest domain (Messias et al 2017). The mean annual temperature varies between 14°C and 28°C, with an annual pluviometric mean of 1,552mm and two distinct seasons: a dry season from March to September and a rainy season from October to February, the climate being classified as Cwb in the Köeppen system (Pedreira & Sousa, 2011).…”
Section: Study Site Animals and Maintenancementioning
confidence: 99%
“…PEIT is a park at a high altitude (900 to 1772 m above sea level), located in the Ouro Preto and Mariana municipalities (20°22′30″–20°30′00″ S and 43°32′30″–43°22′30″ W) 72 , at the southern portion of the Espinhaço Mountain 73 , near the south border of the São Francisco Craton 74 in Minas Gerais State, Southeastern Brazil. It occupies an area of approximately 70 km 2 .…”
Section: Methodsmentioning
confidence: 99%